2019
DOI: 10.1136/ejhpharm-2018-001835
|View full text |Cite
|
Sign up to set email alerts
|

Results of EAHP’s 2018 Survey on Medicines Shortages

Abstract: Aims and objectivesThe aim of the 2018 EAHP Survey on Medicines Shortages was to provide a clearer picture on the issue of medicines shortages, including the impact on hospital pharmacists’ time, budgets and the effect on patient care.MethodsA survey was conducted by the EAHP, collecting information from European hospital pharmacists on the shortage situation in their respective countries. The survey ran from 19 March 2018 to 11 June 2018. Keele University, UK analysed and compared the results to those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 4 publications
1
51
0
2
Order By: Relevance
“…The survey results demonstrate wide variation concerning the time needed to manage a shortage via risk assessment, stretching from 1 to 20 h per week. The literature confirms this variation in Europe (Caulder et al, 2015;Pauwels et al, 2015;Miljkovic et al, 2019). Developing tailor-made measures to mitigate shortages does remain a challenge due to time concerns among some participants.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The survey results demonstrate wide variation concerning the time needed to manage a shortage via risk assessment, stretching from 1 to 20 h per week. The literature confirms this variation in Europe (Caulder et al, 2015;Pauwels et al, 2015;Miljkovic et al, 2019). Developing tailor-made measures to mitigate shortages does remain a challenge due to time concerns among some participants.…”
Section: Discussionmentioning
confidence: 72%
“…Shortages of medicines have been on the rise globally this century (Gray and Manasse, 2012; American Society of Health-System Pharmacists, 2014; The Society of Hospital Pharmacists of Australia, 2017; Root, 2018;Miljkovic et al, 2019;Videau et al, 2019). Due to their multifaceted nature, there are currently over 26 definitions of medicine shortages from manufacturers, wholesalers, regulators, and healthcare providers (De Weerdt et al, 2015;Fox and McLaughlin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Medicine shortages are an everyday occurrence, causing great risk to the continuity of patient care (1,2). Following medicine shortages, providing a suitable, clinically appropriate and safe alternative medicine to a patient is a priority to every health-care professional (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Shortages of medicines have been identified as another factor affecting health-seeking behaviours amongst adolescents. The results are kind of, as the study conducted within the European hospitals wherever ninety percent of respondents indicated that shortages of medicines are a current drawback in delivering the most effective care to patients (Miljković, Gibbons, Batista, Fitzpatrick, Underhill, & Horák, 2019). Shortage of supplies and medicines in Uganda found to be a factor affecting compliance and health-seeking behaviour in hypertensive patients as mentioned by (Musinguzi et al, 2018).…”
Section: Discussionmentioning
confidence: 87%